THE NOMENCLATURE OF PROTOZEAN PARASITES OF MAN - BELTRAN, ENRIQUE (Hospital General, CD MEXICO, DF, MEX, 1950)
In order to determine the best basic native corn vars for a corn-improvement program in the highlands of Mexico, 240 samples from the states of Guanajuato, Jalisco and Michoacan and 98 samples from the Mesa Central were grown in replicated yield trials
GAC MED MEX
Keywords: NOMENCLATURE, PROTOZEAN, PARASITES,MAN; CIENCIAS MEDICAS; PATOLOGIA; PARASITOLOGIA